2012
DOI: 10.4254/wjh.v4.i6.196
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatitis secondary to parenteral amiodarone does not preclude subsequent oral therapy

Abstract: Amiodarone chlorhydrate is a diiodated benzofuran derivative used to treat cardiac rhythm abnormalities�� Hepatotoxicity is a relatively uncommon side effect of amiodarone and symptomatic hepatic dysfunction occurs in less than 1% to 3% of patients taking amiodarone�� We report here on an unusual case of amiodarone-induced hepatotoxicity�� A 29 year old woman with normal liver function was given amiodarone intravenously to treat her atrial fibrillation. She developed acute toxic hepatitis after 24 h�� The intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 9 publications
(10 reference statements)
0
17
0
5
Order By: Relevance
“…If polysorbate 80 is the cause of the acute hepatotoxicity, it would seem prudent for the pharmaceutical industry to find a more suitable diluent. 9,2326 …”
Section: Discussionmentioning
confidence: 99%
“…If polysorbate 80 is the cause of the acute hepatotoxicity, it would seem prudent for the pharmaceutical industry to find a more suitable diluent. 9,2326 …”
Section: Discussionmentioning
confidence: 99%
“…Most patients described in the reviewed cases had evidence of poor forward output, hepatic venous congestion, impaired circulation and acute kidney injury, predisposing them to ischemic hepatitis. Finally, another report by Lahbabi et al ascribes responsibility of liver toxicity to solubilizers such as polysorbate 80 in the IV amiodarone preparation 9. Polysorbate 80 has been implicated in the E-Ferol syndrome characterized by renal failure, hepatosplenomegaly, and jaundice.…”
Section: Discussionmentioning
confidence: 99%
“…The drug shows hepatotoxicity and hepatic dysfunction in humans . A study revealed that an intravenous dose of amiodarone caused hepatotoxicity in a 29‐year‐old woman, but, after termination of this dose, and subsequent start of an oral therapy of amiodarone, hepatotoxicity did not recur . Hepatotoxicity associated with benzofuran derivatives is linked with mitochondrial toxicity, followed by necrosis .…”
mentioning
confidence: 99%